Prof. Sözen talks about the negotiations and peace in Cyprus - December 2015 - Sözen, Ahmet (PIK 2 TV, 2015)
[Abstract Not Available]
Prof. Sözen talks about the negotiations and peace in Cyprus - December 2015. (BİZ, PIK2)
Keywords: Peace in Cyprus; North Cyprus; Negotiations in Cyprus; Cyprus Issue; Cyprus Conflict; Cyprus Dispute; Cyprus Problem; Cyprus Question; Peace Negotiations